Development of an android-based fractional education game with independent character strengthening - Verawati Verawati; Yuniawatika Yuniawatika; Arda Purnama Putra (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2022)
Media use in mathematics learning in elementary schools is crucial One technology-based media that can make it easier for students to learn while playing is educational games. This development research aims to produce an android application in the form of an educational game with independent character strengthening that is feasible and practical to be used as a learning medium for mathematics fractional material for grade 4 elementary school students. This research uses the ADDIE model's research and development, which consists of five stages: analysis,, design, development, implementation, and evaluation. Media feasibility assessments are carried out by material experts, media experts, and teachers. The students assessed the practicality of the medias after using the media at the time of the trial. The data collection instruments used in this study were questionnaires, interviews, observations, and evaluation tests. The results showed that: (1) validation results from material experts, media experts, and teachers show that educational game media is very suitable for use in learning, (2) the results of student response questionnaires in large and small group trials show that practical educational games are used as mathematics learning media for fractional material for grade 4 students, (3) learning outcomes and student independence character increase after learning to use the media.